Role of Methoprene-tolerant in the regulation of oogenesis in Dipetalogaster maxima - Ramos, Fabian (2022)
Juvenile hormone (JH) signalling, via its receptor Methoprene-tolerant (Met), controls metamorphosis and reproduction in insects. Met belongs to a superfamily of transcription factors containing the basic Helix Loop Helix (bHLH) and Per Arnt Sim (PAS) domains. Since its discovery in 1986, Met has been characterized in several insect species. However, in spite of the importance as vectors of Chagas disease, our knowledge on the role of Met in JH signalling in Triatominae is limited. In this study, we cloned and sequenced the Dipetalogaster maxima Met transcript (DmaxMet). Molecular modelling was used to build the structure of Met and identify the JH binding site. To further understand the role of the JH receptor during oogenesis, transcript levels were evaluated in two main target organs of JH, fat body and ovary. Functional studies using Met RNAi revealed significant decreases of transcripts for vitellogenin (Vg) and lipophorin (Lp), as well as their receptors. Lp and Vg protein amounts in fat body, as well as Vg in hemolymph were also decreased, and ovarian development was impaired. Overall, these studies provide additional molecular insights on the roles of JH signalling in oogenesis in Triatominae; and therefore are relevant for the epidemiology of Chagas´ disease.